Separation of Azoxybenzenes and Some Derivatives by High Performance Liquid Chromatography. - Jasim, Hadi Hessen; Al-Zahawi, Suha K; Abed, Dhulfiqar Ali (Al-Nahrain Journal of Science, 2012)
A high performance liquid chromatographic method was used for the Separation and determination of a mixture of Azoxybenzene (diphenyldiazine-1-oxide) together with three of its derivatives; i.e. 4,’4-dinitroazoxy benzene; 4, ’4-dichloroazoxybenzene and 4-chloro-’4-methoxyazoxybenzene.Chromatography was performed at 50C° using a mixture of methanol-water as a mobile phase. The percentage of methanol in this mixture was between (80-90)%. The precision was very high since the error in this study was less than (0.3%) because the relative error of percentage Erel% is between (0.28-0.65) and the detection limit (DL) in this method was equal to (0.2) ng.